Deployment of Cooperative Intelligent Transport System infrastructure along highways: A bottom-up societal benefit analysis for Flanders. (April 2023) - Degrande, Thibault; Vannieuwenborg, Frederic; Verbrugge, Sofie; Colle, Didier
Abstract: The arrival of specific telecommunication technologies has enabled road users and traffic managers to use shared information to coordinate their actions. Cooperative Intelligent Transport Systems (C-ITS) aim to improve road safety, reduce environmental impacts and congestion, and optimize transport efficiency. For this reason, the European Commission and its Member States are explicitly looking forward to connected vehicles to help reach major societal goals in terms of traffic safety (Vision Zero) and traffic emissions (Green Deal). As the necessary roadside infrastructure requires substantial investments from road authorities, societal benefit estimation of C-ITS on these domains is essential within efficient public budget allocation. Therefore, this paper investigates to what extent the societal benefits of roadside unit (RSU) investments in Flanders contribute to obtaining the societal goals, for the upcoming 15 years. It is shown that the contribution of C-ITS with regard to societal goals is rather limited. Adoption of C-ITS in passenger cars is found to be the major limiting factor for benefits. Highlights: Societal C-ITS benefit quantification should take into account the correct baseline. Incremental C-ITS benefits are reduced if legacy ITS infrastructure is present. The penetration of C-ITS in passenger cars is most determinative for benefits. The impact of a single, or interoperable technologies on benefits is substantial. Contribution of C-ITS in reaching European societal goals is limited.